Synthesis and vibration spectroscopy of nano-sized manganese oxides - Mironova-Ulmane, Nina; Kuzmin, Alexei; Skvortsova, Vera N.; Chikvaidze, George; Sildos, Ilmo; Grabis, Janis; Jankovica, Dzidra; Dindune, Antonija P.; Maiorov, Mikhail M. (Polish Academy of Sciences, 2018)
X-ray diffraction, micro-Raman and the Fourier transform infrared spectroscopies as well as magnetometry measurements were performed on nanosized manganese oxides to probe their phase composition and magnetic properties. It was shown that the XRD method is less sensitive to phase composition of manganese oxide samples than spectroscopic methods. While in some samples the XRD method recognised only the manganosite MnO phase, the Raman and FT-IR methods revealed additionally the presence of the hausmannite Mn3O4 phase.
The present study has been supported by the Latvian National Research Program IMIS2. One of us, IS, was supported by MES RF RFMEFI61615X0064.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics